UJI EFEKTIVITAS DAYA ANTHELMINTIK JUS BIJI MENTIMUN (Cucumis Sativum, L) TERHADAP CACING ASCARIDIA GALLI SECARA IN VITRO - Leonov Rianto; Indri Astuti; Ika Prihatiningrum (Jurnal Ilmiah Manuntung, 2016)
Research has been conducted to review the efficacy of anthelmintic on seeing the juice of cucumber seeds ( Cucumis sativum , L ) Against Ascaridia galli by in vitro method . By experimental study was conducted , with samples of seeds of cucumber ( Cucumis sativum , L ) The smoothed and made with 3 concentrations That is 15 % , 30 % and 60 % . The experimental animals used is Ascaridia galli with negative control solution of NaCl 0.9 % and a positive control pyrantel pamoate suspension with concentrations of 0.2 % , 0.4 % and 0.6 % . The analysis of data is probit analysis be adopted . Results Of Research was claimed that the juice of cucumber seeds ( Cucumis sativum , L ) have anthelmintic efficacy against Ascaridia galli with 12.76 % LC50 and LT50 3 hours 4 minutes 39 seconds . Comparising with tables of LD50 value, the obtained dose is 472,59mg / kg and it is in no toxic category.